assume
abc  = 3 first digits
defg = 4 last digits
  step 1:       abc
step 2:  *     80
step 3:  +      1
step 4:  *    250
step 5:  +   defg
step 6:  +   defg
step 7:  -    250  
step 8:  /      2
  step 6: Result = ((abc*80)+1)*250 + 2*defg
step 7: Result = ((abc*80)+1)*250 + 2*defg - 1*250
    <=> Result = ((abc*80)+1-1)*250 + 2*defg
    <=> Result = (abc*20000) + 2*defg
    <=> Result = 2*(abc*10000 + defg)
step 8: Result = 2*(abc*10000 + defg) / 2
    <=> Result = abc*10000 + defg
  in a simpler way      abc
*  10000
=abc0000
+   defg
=abcdefg
The trick is to hide the fact that you multiply by 10000
  ;-) Baltazar  

PS: It's college maths...